The Influence of Job Insecurity, Direct Financial Compensation, Transformational Leadership, and Work Quality on Human Resource Performance (MI Ma’arif Kliwonan) - Kwee, Saniayuen; Maulidiyah, Ibnatul; Wulandari, Rizky Wahyu; Hikmah, Noor (Proceedings Series on Social Sciences & Humanities, 2025)
The purpose of this study is to examine how job insecurity, direct financial compensation, transformational leadership, and work quality human resource (HR) performance at MI Ma'arif Kliwonan Wonosobo. The reason for choosing this location as the research site is due to indications of declining human resource performance at the institution. This study highlights the importance of factors such as job insecurity, financial compensation, leadership, and work quality in influencing HR performance in educational institutions, particularly in terms of generating a positive work atmosphere and enhancing the productivity of teachers. This study employed a quantitative approach that included several linear regressions. Data were acquired by distributing questionnaires to teachers at MI Ma'arif Kliwonan Wonosobo using a random sampling technique. Random sampling was chosen to ensure that each respondent had an equal opportunity to participate, allowing the research results to be more accurately generalized to the population. SPSS was used to analyze the data in this study. The findings of this study can be used to improve the efficacy of human resource management in educational institutions by taking into account key aspects that drive performance. The results of this study show that job insecurity and work quality have a positive and significant impact on HR performance, whereas direct financial compensation has a negative but significant effect. Transformational leadership does not have a significant influence. Simultaneously, these four variables significantly affect HR performance. These findings imply the need for improving HR management in educational institutions by considering these key factors to enhance productivity and create a conducive work environment.